PENGEMBANGAN EDU KOMIK SEBAGAI BAHAN AJAR BERBASIS PENDIDIKAN KARAKTER PADA MATERI INTERAKSI MAHLUK HIDUP DAN LINGKUNGANNYA DI SEKOLAH MENENGAH PERTAMA - Zuli Lailatul Fajriah; Evita Anggereini (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2016)
ABSTRACT. This experiment uses a model of procedural development of ADDIE instructional design. Data were obtained in the form of quantitative data obtained through a questionnaire. The data obtained in the subsequent descriptive-quantitative analysis. Validation by media experts to obtain a score of 60 with a percentage of 93.75% with interpretation of